Analisis Break Even Point (BEP) Sebagai Alat Perencanaan Laba Pada Usaha Gorengan KUD Kota Sorong - Novelia Kewetary; Rikoles Latumahina; Fret Danni Iek; Elsa Rumetwa; Mentina Pasaribu; Victor Sipayung; Daud Hiluka; Susana M. W. Muskitta (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
The purpose of this research is to analyze the break event point (BEP) as a profit planning tool in the Various Kinds of Fried Kud business. This research uses a quantitative approach involving direct surveys with question and answer interview techniques to traders. This approach makes it possible to obtain primary data regarding sales volume, selling price, fixed costs and variable costs related to the Various Kinds of Fried Kud business. The results of the research show that the January calculation explains that the BEP (rupiah) for fried food sales was IDR 24,902,723.74,- and the BEP in units was 24,903 units. Break Even Point (BEP) shows the point where the income from sales is equal to the total costs, so that you do not experience a loss, but instead make a profit. In February, the calculation results show that the BEP (rupiah) for fried food sales was IDR 27,004,219.41,- and the BEP in units was 27,004 units. Break Even Point (BEP) shows the point where the revenue from sales is equal to the total costs, so there is no loss, but rather a profit. These results indicate that profit planning has increased in February.